Paths to Motherhood for Women with Cystic Fibrosis. Issue 3 (May 2022) - Bray, Leigh Ann; Campbell, Caitlin Marley; Brown, Janet; Ladores, Sigrid
Abstract: Purpose: Cystic fibrosis (CF) is no longer a disease limited to childhood. With medical advancements, many of those with CF live into adulthood and have similar life goals as their non-CF peers. Most women with CF want to become mothers. However, available options and the related decision-making process is not well understood. The purpose of this study was to explore the decision-making framework of women with CF to better understand the factors they consider when deciding on a path to motherhood. Study Design and Methods: Qualitative interviews were performed using a grounded theory approach. Inclusion criteria were women with CF who became mothers through biological pregnancy, adoption, or gestational surrogacy. Results: Twenty-five mothers with CF were interviewed. A distinct decision-making process was identified through which women started with a desire for motherhood, assessed several factors, then eventually took the path they felt was right for them and their family. Clinical Implications: Our findings provide women with CF a framework that other women with CF have used to assist in making decisions about their reproductive options. Conversations about family planning should occur early and regularly between women with CF and their health care providers. The decision-making process to achieve motherhood for women with a chronic illness, such as CF, includes consideration of unique factors that should be included in clinical conversations. Abstract : Cystic fibrosis is no longer a disease limited to childhood. With medical advancements, many patients with cystic fibrosis live into adulthood and consider becoming mothers, however available options and their reproductive decision-making process are not well understood. In this study women with cystic fibrosis describe their decision-making as they considered various options for motherhood.